PEMBELAJARAN KETERAMPILAN MENULIS NASKAH DRAMA DENGAN MEDIA GAMBAR PADA SISWA SMA NU-1 MODEL SUNGELEBAK KARANGGENENG LAMONGAN - Mustofa Mustofa; Bisarul Ihsan (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2021)
This scientific writing aims to examine learning the ability to write drama scripts using image media. Based on the explanations above, it can be stated that the research objectives are to determine student activity, teacher activity, student responses, and student learning completeness in writing drama scripts using picture media. This research was conducted in Class XI SMA NU-1 MODEL Sungelebak Karanggeneng, Lamongan Regency, amounting to 41 students who have different characteristics. This research was conducted collaboratively which was carried out based on teacher activities, student activities, and students' abilities in writing drama scripts using picture media. Data collection techniques used observation and tests. Based on the research results, it is known that learning with picture media is very effective to be applied to the material of writing drama scripts in terms of: (1) student activity is at an effective level with a positive activity percentage of 93.745%. (2) teacher activity is at a very effective level with an average active teacher activity of 90.93 which is in the good category. (3) student responses are at the effective level with a positive response percentage of 86.178%. (4) student learning completeness is at an effective level with classical learning completeness of 90.243%, so that it meets classical completeness ≥70. With the research results, it can be taken into consideration by all educators to apply learning to write drama scripts using image media in learning activities. Abstrak Karya tulis ilmiah ini bertujuan untuk meneliti pembelajaran kemampuan menulis naskah drama dengan media gambar. Penelitian ini dilaksanakan pada Kelas XI SMA NU-1 MODEL Sungelebak Karanggeneng Kabupaten Lamongan yang berjumlah 41 siswa dengan karakteristik berbeda-beda. Penelitian ini dilakukan secara kolaboratif yang dilaksanakan berdasarkan aktivitas guru, aktivitas siswa, dan kemampuan sisiwa dalam menulis naskah drama dengan menggunakan media gambar. Teknik pengumpulan data yang digunakan observasi dan tes. Berdasarkan hasil penelitian diketahui bahwa pembelajaran dengan media gambar sangat efektif untuk diterapkan pada materi menulis naskah drama ditinjau dari: (1) aktivitas siswa berada pada tingkat efektif dengan presentase aktivitas positifnya sebesar 93,745%. (2) aktivitas guru berada pada tingkat sangat efektif dengan rata-rata aktivitas guru aktif sebesar 90,93 yang termasuk dalam kategori baik. (3) respon siswa berada pada tingkat efektif dengan presentase respon positifnya sebesar 86,178%. (4) ketuntasan belajar siswa berada pada tingkat efektif dengan ketuntasan belajar klasikal sebesar 90,243%, sehingga memenuhi ketuntasan klasikal ≥70. Dengan adanya hasil penelitian, maka bisa dijadikan pertimbangan oleh semua pendidik untuk menerapkan pembelajaran menulis naskah drama dengan menggunakan media gambar dalam kegiatan pembelajaran. Kata Kunci: Menulis, Naskah Drama, Media Gambar